No barriers : a blind man's journey to kayak the Grand Canyon - Weihenmayer, Erik; Levy, Buddy, 1960- (Thomas Dunne Books, St. Martin's Press, 2017)
"No Barriers is about my journey since coming down from Mt. Everest in 2001, and the path to where I am today. It is the story of my own life, the personal and professional struggles in the pursuit of growth, learning, and family, as well as a dream to kayak one of the world's great rivers as a blind athlete. It is also about the many people I've encountered along the way who possess what I call a "No Barriers" mindset, who live a No Barriers life. It highlights these pioneers who give those around them the courage to do great things. People who have risked failure, transcended their personal barriers, and shown others a way forward: scientists and innovators, artists and musicians, climbers and adventurers, activists and soldiers. No Barriers is a way of living, and it exists in all of us, like a deep internal light. But sometimes through trauma, loss, isolation, and disillusionment, people get shoved into a dark place, and that light is almost extinguished. Making hard choices is what feeds that light, and becomes the energy we need to propel us forward. This book is about making the hard choices to fuel that flickering light, so that we can ignite with purpose and become our very best selves"--